Durability Properties of Palm Oil Fuel Ash Self Compacting Concrete - Ofuyatan, T.; Olutoge, F. A.; Olowofoyeku, A. (Engineering, Technology & Applied Science Research, 2015)
Self Compacting Concrete (SCC) is a new innovation in technology that can flow readily into place under its own self weight and fill corner areas of reinforcement structures without the need to vibrate and without segregation of its constitute. The problem of durability of concrete structures due to inadequate compaction by skilled workers has become a source of concern globally. The shortage of skilled manpower, noise and vibration of equipment on construction sites has led to the development of self compacting concrete. This paper presents an experimental study on the durability properties of Self Compacting Concrete with partial placement of Palm Oil Fuel Ash (POFA). Twelve POFA self-compacting concretes of various strength grades were designed at varying percentages of 0, 5, 10, 15, 20, 25 and 30%. The concrete with no placement of ash served as control. Conplast SP432MS was used as superplasticiser in the mix. The experiments are carried out by adopting a water-powder ratio of 0.36. Workability of the fresh concrete is determined by using tests such as: slump flow, T50, V-funnel and L-Box tests. The durability of concrete is tested by acid resistance, sulphate attack and saturated water absorption at the age of 14, 28, 56 and 90 days.